Uji Hedonik Kerupuk yang Disubtitusi dengan Tepung Tulang dari Jenis Ikan Berbeda - Marzatul Kiflah; Lia Handayani; Rulita Maulidya (Jurnal TILAPIA, 2024)
This study was conducted to find out how the effect of different fish bone meal substitution ingredients on the hedonic test properties of crackers. This study uses an experiment method  with 2 factors, namely fish bone type factors (tuna fish bones and starry triggerfish bones), fish bone meal comparison factors (10%, 15% and 20%). The hedonic test (preference test) is used to measure organoleptic properties (taste, aroma, color, and texture). Nonparametric data were analyzed using the Kruskall-Wallis method  and continued  with the Mann-Whitney test  if there were significant differences and the Bayes test was carried out  to determine the best treatment. Based on the results of the study, it can be concluded that panelists still like crackers added with tuna and starry triggerfish bone meal in all treatments. However, treatment B which added  starry triggerfish bone meal by 10% resulted in crackers that were preferred over other treatments. The taste preference values for taste, aroma, color, and texture were 8.36±0.15, 8.23±0.10, 8.18±0.05, and 8.19±0.05 respectively.